Toward Complexity Measures for Systems Involving Human Computation. - Chang, Remco.; Crouser, R. Jordan.; Hescott, Benjamin J. (Tufts University. Tisch Library., 2017)
This paper introduces the Human Oracle Model as a method for characterizing and quantifying the use of human processing power as part of an algorithmic process. The utility of this model is demonstrated through a comparative algorithmic analysis of several well-known human computation systems, as well as the definition of a preliminary characterization of the space of human computation under this model. Through this research, we hope to gain insight about the challenges unique to human computation and direct the search for efficient human computation algorithms.